Isolation of Ferulic Acid from Wheat Bran with a Deep Eutectic Solvent and Modified Silica Gel. (13th August 2017) - Li, Guizhen; Zhu, Tao; Row, Kyung Ho
ABSTRACT: Five deep eutectic solvents (DESs) were synthesized with choline chloride and glycerol at ratios from 1:1 to 1:5 and used to extract ferulic acid from wheat bran. The DES with choline chloride:glycerol at a 1:2 molar ratio (DES-2) provided the highest extraction yield. The optimal extraction conditions for DES-2 were obtained using response surface methodology with a yield of 5.86 mg · g −1 ferulic acid. The DES-2 was used to modify silica gel and purify ferulic acid from wheat bran by solid-phase extraction (SPE). The yields were compared for silica gel and silica gel modified with ionic liquid. The recoveries for ferulic acid were 64.1, 89.7, and 80.3%, respectively. Silica gel modified with DES-2 provided the highest recovery. The materials were characterized by infrared spectroscopy and scanning electron microscopy. The DESs were used as extraction solvents and to modify silica gel for SPE, expanding their use in the isolation of ferulic acid from wheat bran.